Avaliação da sensibilidade de Colossoma macropomum G. Cuvier, 1818 (Tambaqui) como espécie sentinela para o herbicida trifluralina - Silva, Jaqueline Maria da (2013)
Amazonian Tambaqui (Colossoma macropomum) is a commercial important fish species that is intensively cultivated in rice fish-cultures in a variety of water paddies in the area of the São Francisco river in the northeast of Brazil. Commercial formulations of herbicides containing Trifluralin (α,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine) are commonly used to control weed on the rice fields of the area. The present study aimed to investigate the sensitivity of Colossoma macropomum to trifluralin using biomarkers to understand the effects of an acute exposure to this substance. On the in vivo toxicity tests, C. macropomum juvenile were exposed to four concentrations of trifluralin: 0.74, 1.5, 2.23 and 3.0 μmols / L for 96 hours, and compared with negative, positive controls and solvent, respectively. The herbicide trifluralin shows a dose-dependent inhibition profile on the brain C. macropomum cholinesterase activity. On the highest trifluralin concentration was observed a drop in the cholinesterase activity around 62 % and the inhibition of the muscle was 80 % at the highest concentration tested. The estimated value of 96 h LC50 for trifluralin was 1.25 μmols / L. In vitro assays had shown that brain cholinesterase-ChE C.macropomum has a moderate sensitivity toward trifluralin (2.34 μmols / L) whereas the sensitivity to the carbamate eserine is much higher (0.158 μmols / L). In order to get the apparent kinetic constants for C.macropomum brain cholinesterase, kinetic assays were performed on brain homogenate in the presence of acetylthiocholine as substrate. The kinetic results in the presence of acetylthiocholine as substrate, the brain homogenate containing activity were 0.043 ± 0.015 mmol / L and 0.301 ± 0.014 for mmol.min-1.mg-1 protein Kapp m and Vapp max apparent kinetic constants, respectively. We also evaluated the mutagenic, genotoxic and apoptotic exposure of C. macropomum juvenile trifluralin. In the Comet assay, erythrocytes analyzed, compared to the negative control showed induction of DNA damage at all concentrations tested. The higher frequency of micronuclei and high numbers of apoptotic cells were observed in fish treated with concentrations of 1.5 μmols / L with a significant effect (p < 0.01). The results of this study indicate that brain ChE C. macropomum is a reliable biomarker for use in environmental monitoring of pesticides in the delta of the São Francisco river. It was also confirmed the genotoxic and apoptotic trifluralin at concentrations from 1.5 μmols / L for juvenile C. macropomum. (Note: check some nomeclaturas in the original summary because lost formatting in this field)